N,N-Dimethyl-D-erythro-Sphingosine Inhibits Store-Operated Ca2+ Entry in U937 Monocytes - Ji-Yeong Jo; Hyo-Lim Kim; Yun-Kyung Lee; Hideaki Tomura; Yoe-Sik Bae; Fumikazu Okajima; Dong-Soon Im (Elsevier, 2008)
Calcium is a ubiquitous second messenger that controls a broad range of cellular functions, and store-operated calcium entry (SOCE) is the primary mechanism of regulated Ca2+ entry in non-excitable immunocytes. In this study, we found that N,N-dimethyl-D-erythro-sphingosine (DMS) inhibited SOCE. In U937 cells, treatment with DMS for 2 h inhibited thapsigargin-induced SOCE by about 70%. DMS inhibited SOCE in a concentration-dependent manner when it was added to the cells after SOCE reached a plateau. DMS-induced SOCE inhibition was also confirmed by the Mn2+-quenching method, which monitors only Ca2+ influx. Because sphingosine kinase inhibitors or protein kinase C (PKC) inhibitors could not mimic the SOCE inhibition, sphingosine kinase and PKC could be excluded as targets of DMS-induced inhibition of SOCE. Furthermore, disruption of lipid rafts with methyl-β-cyclodextrin and bacterial sphingomyelinase did not influence DMS-induced inhibition of SOCE. DMS-induced inhibition of SOCE in U937 human monocytes is a unique observation and could serve as a basis to study modulation of intracellular Ca2+ concentration by sphingolipids, although the precise mechanism should be elucidated in the future. Keywords:: dimethylsphingosine, dimethylphytosphingosine, sphingosine, store-operated Ca2+ entry, calcium